2022
DOI: 10.3390/civileng3010003
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Reliability of Scaling Down Techniques Used in Direct Shear Tests to Determine the Shear Strength of Rockfill and Waste Rocks

Abstract: The determination of shear strength parameters for coarse granular materials such as rockfill and waste rocks is challenging due to their oversized particles and the minimum required ratio of 10 between the specimen width (W) and the maximum particle size (dmax) of tested samples for direct shear tests. To overcome this problem, a common practice is to prepare test samples by excluding the oversized particles. This method is called the scalping scaling down technique. Making further modifications on scalped sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…Using a standard direct shear test box (6 cm for most cases) with field materials and respecting the minimum required specimen sizes to d max ratio are impossible. Scaling down techniques are thus employed by removing oversized particles during sample preparation to make laboratory tests possible [16,[58][59][60][61][62][63][64][65][66][67]. For most cases, the d max of the resulting samples can still be too large compared to any available standard or nonstandard direct shear test apparatus.…”
Section: Previous Laboratory Tests On Sse Of Direct Shear Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a standard direct shear test box (6 cm for most cases) with field materials and respecting the minimum required specimen sizes to d max ratio are impossible. Scaling down techniques are thus employed by removing oversized particles during sample preparation to make laboratory tests possible [16,[58][59][60][61][62][63][64][65][66][67]. For most cases, the d max of the resulting samples can still be too large compared to any available standard or nonstandard direct shear test apparatus.…”
Section: Previous Laboratory Tests On Sse Of Direct Shear Testsmentioning
confidence: 99%
“…For most cases, the d max of the resulting samples can still be too large compared to any available standard or nonstandard direct shear test apparatus. The minimum required specimen size to d max ratio of 10 [42,68] has thus been universally used in direct shear tests [11,16,62,[69][70][71][72][73][74] even though the validity of this minimum required value of 10 has never been verified. In other words, it remains unclear if the SSE of direct shear tests is eliminated with specimens having a width to d max ratio of 10.…”
Section: Previous Laboratory Tests On Sse Of Direct Shear Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous research has been reported about the effect of these techniques on the shear strength of granular materials, the results widely vary up to the point of being contradictory. While some studies have indicated that shear strength decreases with grain size [Marachi et al, 1972, Ovalle et al, 2014, Varadarajan et al, 2003, Xiao et al, 2014, Zeller and Wullimann, 1957, others have shown the opposite behavior [Al-Hussaini, 1983, Cao et al, 2020, Deiminiat and Li, 2022, Linero et al, 2007. The sources of this apparent contradiction are presumably found in several sample and testing characteristics, and inherent material properties.…”
Section: Introductionmentioning
confidence: 99%
“…It follows, by analogy, that friction angles of field samples, when evaluated using the scalping scaling-down technique, can be accurately predicted. In contrast, predictions based on the parallel scaling-down technique may be deemed unreliable for active mines or real-case scenarios [36].…”
Section: Introductionmentioning
confidence: 99%